EVALUASI PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) (Studi Kasus : Pembangunan Gedung Workshop Cikarang) - Hakim, Nurkholis; Wibowo, Kartono; Antonius, Antonius (Jurnal Teknik Sipil dan Arsitektur, 2026)
Occupational safety and health are crucial aspects in the implementation of construction projects, especially large-scale projects such as the construction of the Workshop Building in Cikarang. Workplace accidents that still frequently occur on-site highlight the importance of evaluating the implementation of the Occupational Safety and Health Management System (OSHMS). This study aims to measure the level of OSHMS implementation, identify the barriers to its implementation, and evaluate the strategies used to overcome these barriers. The method used in this study is descriptive evaluative with a quantitative approach, where data was collected through the distribution of questionnaires to 80 respondents consisting of workers and project management teams. The research instruments were tested using validity and reliability tests, and the results were analyzed using mean calculations and the Relative Importance Index (RII). Data was processed using SPSS software. The research results indicate that the level of SMK3 implementation is in the â€œVery Goodâ€ category, with the highest average score of 4.7 and an RSI of 0.94 on the indicator of understanding and implementation of safety procedures. The obstacles faced were categorized as â€œLess Hindering,â€ with the lowest average score of 1.89 and an RSI of 0.38 related to management commitment to SMK3. Meanwhile, strengthening strategies such as safety briefings and SOP evaluations were categorized as â€œVery Effective,â€ with the highest average score of 4.63 and an IKR of 0.925. The conclusion of this study is that the implementation of SMK3 in this project has been optimal, with minimal obstacles and effective control strategies